2016
DOI: 10.1152/ajpcell.00009.2016
|View full text |Cite
|
Sign up to set email alerts
|

Chronology of UPR activation in skeletal muscle adaptations to chronic contractile activity

Abstract: The mitochondrial and endoplasmic reticulum unfolded protein responses (UPR(mt) and UPR(ER)) are important for cellular homeostasis during stimulus-induced increases in protein synthesis. Exercise triggers the synthesis of mitochondrial proteins, regulated in part by peroxisome proliferator activator receptor-γ coactivator 1α (PGC-1α). To investigate the role of the UPR in exercise-induced adaptations, we subjected rats to 3 h of chronic contractile activity (CCA) for 1, 2, 3, 5, or 7 days followed by 3 h of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
60
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 66 publications
12
60
2
1
Order By: Relevance
“…; Memme et al. ), we observed that PGC‐1 α , a master regulator of mitochondrial biogenesis, was upregulated by CCA in skeletal muscle by day 7, which was supported by the increased whole muscle COX activity. Although COX I and COX IV protein levels were changed in a time‐dependent manner, they showed similar protein expression patterns with PGC‐1 α , suggesting the likelihood of concurrent CCA‐induced mitochondrial biogenesis.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…; Memme et al. ), we observed that PGC‐1 α , a master regulator of mitochondrial biogenesis, was upregulated by CCA in skeletal muscle by day 7, which was supported by the increased whole muscle COX activity. Although COX I and COX IV protein levels were changed in a time‐dependent manner, they showed similar protein expression patterns with PGC‐1 α , suggesting the likelihood of concurrent CCA‐induced mitochondrial biogenesis.…”
Section: Discussionsupporting
confidence: 73%
“…; O'Leary and Hood ; Memme et al. ). Our findings provide evidence that the autophagy and lysosomal systems adapt prior to, or concomitant with, mitochondrial changes in skeletal muscle exposed to chronic contractile activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to provide a more complete documentation of the time course of UPR activation in response to acute exercise, and the adaptations to training, recent work in our laboratory has examined the activation of both the UPR ER and the UPR mt in response to repeated bouts of exercise of contractile activity in an animal model. Our data indicate that both UPRs are activated in the early stages of the contractile activity training program, preceding the adaptive responses in mitochondrial biogenesis and autophagy 88 . It should be noted that PGC-1α has been shown to be induced by, and to regulate, UPR signaling in an ATF6-dependent manner, indicating an integrated link between UPR and mitochondrial biogenesis pathways 85 .…”
Section: Unfolded Protein Response Signalingmentioning
confidence: 67%